Assessing the Impact of Isoniazid Preventive Therapy (IPT) on Tuberculosis Incidence and Predictors of Tuberculosis among Adult Patients Enrolled on ART in Nekemte Town, Western Ethiopia: A Retrospective Cohort Study - Tiruneh, Gemechu; Getahun, Alemayehu; Adeba, Emiru (Interdisciplinary Perspectives on Infectious Diseases, 2019)
Background. Isoniazid preventive therapy is a prophylactic treatment used in the prevention of active tuberculosis. It is known to be most effective in preventing tuberculosis in patients with positive tuberculin skin test. Methods. A retrospective cohort study centering on two institutions in Nekemte town, Western Ethiopia, was employed. Secondary data of 600 medical records were analyzed by Cox regression. Result. Tuberculosis incidence among the Isoniazid treated group was 1.98 per 100 person-years and 4.52 per 100 person-years in the untreated group. CD4 cell count, clinical staging, body mass index (BMI), not using cotrimoxazole, body weight, and functional status were significant predictors of tuberculosis risk. Isoniazid preventive therapy use was associated with 55% reduction of tuberculosis incidence. Conclusion. Isoniazid preventive therapy use was associated with significant reduction in tuberculosis incidence, even in the absence of Tuberculin Skin Test (TST). Therefore, isoniazid preventive therapy (IPT) coverage should be used more widely, with special emphasis given to patients at higher risk of tuberculosis. The study shows that the absence of TST testing should not be a limitation.